(untitled) (Psychology Travelogs, 2025)
The article presents an analysis of psychological and pedagogical research on the issue of deviant behavior in adolescents. Deviant behavior among adolescents is one of the pressing problems in modern psychology, raising concerns in society. The concepts are clarified as follows: deviant behavior is understood as a system of actions that deviate from generally accepted norms (norms of mental health, law, culture, morality, etc.); deviation is seen as negative forms of deviations; and deviant personality is defined as a set of asocial and immoral views internalized by an individual, which do not meet social expectations and eventually become the individual’s social position, hindering self-actualization, personal growth, and leading to a deviant lifestyle. The relationship between age-specific features of adolescence and manifestations of deviant behavior is explored. It is demonstrated that during this period, adolescents face numerous challenges, such as identity crises, the need for recognition, and the search for their own «self». The article examines the main causes of deviant behavior, including family, social, and personal factors. It is established that the most common types of deviant behavior among adolescents today include criminal activity, alcoholism, drug addiction, substance abuse, and suicide. Deviant behavior negatively impacts the socialization process of youth, reduces the quality of life for adolescents, creates conflicts in families and schools, and fosters the development of asocial tendencies. Typical manifestations of deviant behavior, such as aggression, illegal actions, and the use of psychoactive substances, are analyzed. Special attention is given to prevention and correction methods aimed at reducing the risk of deviations during adolescence. Preventive work is based on studying the causes of behavioral deviations, planning preventive measures through pedagogical diagnostics, and considering the specific characteristics of schools and group development. In psychocorrectional work, cognitive, emotional-volitional methods, and behavioral methods are employed to address deviant behavior effectively.